2011
DOI: 10.1093/bja/aer063
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intrathecal infusion of gabapentin prevents nerve ligation-induced pain in rats

Abstract: We showed a preventative effect of intrathecal gabapentin on the development of nerve injury-induced mechanical allodynia and thermal hyperalgesia. Our data suggest that continuous intrathecal gabapentin may be considered as an alternative for the prevention of nerve injury-induced pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…For instance, the anti-nociceptive and anti-allodynic effectiveness of GBP has been widely supported by studies in animal models of many types of pain induced by peripheral nerve injury such as spinal nerve ligation [47][48][49][50], chronic compression injury [51][52][53][54][55][56] and spared nerve injury [57,58]. Moreover, GBP has also been demonstrated to have anti-allodynic and anti-hyperalgesic effects in animal models of diabetic neuropathy [29] and postherpetic neuralgia [59].…”
Section: Gabapentinoid Insensitivity In Central Neuropathic Pain Of Tmentioning
confidence: 99%
“…For instance, the anti-nociceptive and anti-allodynic effectiveness of GBP has been widely supported by studies in animal models of many types of pain induced by peripheral nerve injury such as spinal nerve ligation [47][48][49][50], chronic compression injury [51][52][53][54][55][56] and spared nerve injury [57,58]. Moreover, GBP has also been demonstrated to have anti-allodynic and anti-hyperalgesic effects in animal models of diabetic neuropathy [29] and postherpetic neuralgia [59].…”
Section: Gabapentinoid Insensitivity In Central Neuropathic Pain Of Tmentioning
confidence: 99%
“…Other analgesics, such as adenosine, sufentanil, alfentanil and morphine have all been tested intrathecally in animal studies to examine their potential neurotoxicity (Chiari et al, 1999;Sabbe et al, 1994;Westin et al, 2010). Recently, chronic intrathecal infusion of minocycline or gabapentin has been reported to cause no grossly neurotoxicity in animal studies (Chu et al, 2011;Lin et al, 2007), supporting the intrathecal use of these agents for pain management. …”
Section: Intrathecal Neurotoxicity Studiesmentioning
confidence: 88%
“…A point mutation of the arginine 217 of 2 -1 subunit, which is critical for gabapentin binding (Wang et al, 1999), was found to cause a loss of gabapentin-induced analgesia (Field et al, 2006). Recently, chronic intrathecal infusion of gabapentin was found to prevent nerve ligation-induced mechanical allodynia and thermal hyperalgesia without causing obvious neuropathological changes in spinal cord and cauda equine (Chu et al, 2011). Gabapentin has been found to attenuate morphine-induced tolerance (Lin et al, 2005) and this finding may encourage the combined use of gabapentin with morphine in the treatment of neuropathic pain.…”
Section: 2 Subunit Of Camentioning
confidence: 99%
“…This subunit is the binding site for gabapentinoid drugs in the dorsal horn. In preclinical models, gabapentin and pregabelin have been shown to have potent effect in a variety ofhyperalgesic pain [175][176][177][178] Preclinical results indicate adequate spinal pK with a very hydrophilic cLogP (-1.13). In a recent study, however, it was unexpectedly reported that intrathecal infusion of gabapentin failed to alter pain assessments in human patients suffering from a variety of neuropathic and non-neuropathic pain states [179].…”
Section: Future Directions For Spinal Calcium Channel Blockersmentioning
confidence: 99%